(untitled) (Scientific journal of the Fergana State University, 2023)
It is known that the study of dam lakes in the organization of special monitoring in order to ensure their stability and reduce their danger allows to develop science-based measures, the possibility of preventing floods caused by dam failures for various reasons, and reduce their socio-economic and moral damage. At the same time, one of the important issues is to study the regularities of dam lakes and their genesis. To this end, this article prioritizes the study of the formation and genesis of dam lakes. To achieve the set goal, the article uses hydrometeorological analysis, hydrological and hydrogeological calculations, and geographical similarity methods. In many cases, as a result of physiographic processes occurring in mid-mountainous and high-mountainous areas, river valleys are blocked by rocks of different sizes, landslides, rockslides, landslide and avalanche rocks and cause the formation of natural dams. According to the conditions of formation of these dams, they cause the occurrence of landslide-tectonic, glacial, moraine, landslide and avalanche lakes, and we call such lakes by the general name "dam lakes". The origin of dam lakes determines their sharp difference from each other in shape, size and volume of water. Therefore, when studying dammed lakes, it is important to take into account their genetic characteristics.